The impact of agricultural green finance on the level of agricultural green development - Aihua Tong; Huawei Niu; Lili Jiang; Yifeng Wang (PLoS ONE, 2025)
Agricultural green finance is an important means to boost the development of agricultural green. Based on the panel data of 30 provinces in China from 2011 to 2021, this paper theoretically discusses the impact of agricultural green finance on the level of agricultural green development and conducts an empirical study by using the two-way fixed effect model and panel threshold model. The empirical findings show that agricultural green finance can significantly improve the level of agricultural green development mainly through facilitating the level of agricultural green technology innovation. The promoting effect of agricultural green finance on the level of agricultural green development is remarkable in the eastern region and non-major grain-producing areas, but not obvious in the central and western regions and major grain-producing areas. Indeed, the impact has a single threshold effect with environmental regulation as the threshold. Therefore, efforts should be made to improve the level of agricultural green development from the following aspects: vigorously developing agricultural green finance; promoting agricultural green technology innovation; strictly implementing environmental protection policies; and designing appropriate environmental regulation zones.